Development of Visuo-Auditory Integration in Space and Time - Gori, Monica; Sandini, Giulio; Burr, David (Frontiers in Integrative Neuroscience, 2012)
Adults integrate multisensory information optimally (e.g., Ernst and Banks, 2002) while children do not integrate multisensory visual-haptic cues until 8–10 years of age (e.g., Gori et al., 2008). Before that age strong unisensory dominance occurs for size and orientation visual-haptic judgments, possibly reflecting a process of cross-sensory calibration between modalities. It is widely recognized that audition dominates time perception, while vision dominates space perception. Within the framework of the cross-sensory calibration hypothesis, we investigate visual-auditory integration in both space and time with child-friendly spatial and temporal bisection tasks. Unimodal and bimodal (conflictual and not) audio-visual thresholds and PSEs were measured and compared with the Bayesian predictions. In the temporal domain, we found that both in children and adults, audition dominates the bimodal visuo-auditory task both in perceived time and precision thresholds. On the contrary, in the visual-auditory spatial task, children younger than 12 years of age show clear visual dominance (for PSEs), and bimodal thresholds higher than the Bayesian prediction. Only in the adult group did bimodal thresholds become optimal. In agreement with previous studies, our results suggest that also visual-auditory adult-like behavior develops late. We suggest that the visual dominance for space and the auditory dominance for time could reflect a cross-sensory comparison of vision in the spatial visuo-audio task and a cross-sensory comparison of audition in the temporal visuo-audio task.